PENGARUH METODE FERMENTASI DAN PENAMBAHAN URINE KELINCI TERHADAP KUALITAS PUPUK ORGANIK CAIR - David Richard Hendarto; Dina Rotua Valentina Banjarnahor (The University of Lampung, 2021)
The Minang Bangkit Merbabu Farmer Group use organic materials and produce their own liquid organic fertilizer. This liquid organic fertilizer is made of varied ingredients: rabbit urine, cow's milk, free-range chicken eggs, palm sugar, coconut water, pineapple, shrimp paste, bamboo roots, ginger, and turmeric. Composting is strongly affected by pH and aeration method. Liquid organic fertilizer made by farmers usually have an initial pH of around 3.7. This mixture was usually composted using semi-anaerobic method. Through this study, we wanted to find out whether different methods of aeration and addition of rabbit urine would result in different liquid organic fertilizer quality. The quality of liquid organic fertilizer includes C-organic, total nitrogen, total phosphorus and total potassium. The experiment was designed as a factorial randomized block design. There were 2 factors tested: rabbit urine volume and aeration method. There were two levels of rabbit urine volume : original and modified ones. There were three levels of aeration method: aerobic, semi-anaerobic, and anaerobic. In total, there were six treatments and four replication for each treatment. The results of the analysis showed that composting with the aerobic method at the original rabbit urine volume could increase the concentration of nutrient content so that it gave the highest yield. It is different from composting at a modified rabbit urine volume, because the highest yield is in the anaerobic method. Keywords: aerated, organic, rabbit urine volume